The Potential of Acorus calamus L. in The Ethnobotany of The Malay Ethnic Communities in Riau Province - Wahyuni, Sri; Herru, Yoan De Nanda; Chahyadi, Ennie; Afidah, Mar’atul; Fadilaturahmah (Biosfer: Jurnal Tadris Biologi, 2026)
Acorus calamus L. is a medicinal plant traditionally used by Malay ethnic communities in Riau Province, Indonesia. However, studies integrating ethnobotanical knowledge with phytochemical evidence are still limited. This study aimed to examine the traditional utilization of Acorus calamus and identify its secondary metabolites as scientific support for its medicinal use. A mixed-method approach was applied by combining qualitative ethnobotanical inquiry with experimental phytochemical screening. Ethnobotanical data were collected through interviews, observation, and documentation involving a traditional healer in Pengambang Jaya Village, Riau Province. Phytochemical analysis was conducted on methanolic extracts of the rhizome using standard qualitative screening methods. The results showed that the rhizome of Acorus calamus is mainly used as a traditional remedy for fever. Phytochemical screening revealed the presence of phenolics, flavonoids, alkaloids, and triterpenoids, while steroids and saponins were not detected. These findings indicate that Acorus calamus contains bioactive compounds associated with medicinal properties and support its traditional use. The study highlights the importance of integrating traditional knowledge with scientific validation in ethnobotanical research. Potensi Acorus calamus L. dalam Etnobotani Komunitas Etnis Melayu di Provinsi Riau ABSTRAK:  Acorus calamus L. merupakan tanaman obat yang secara tradisional dimanfaatkan oleh masyarakat etnis Melayu di Provinsi Riau, Indonesia. Namun, penelitian yang mengintegrasikan pengetahuan etnobotani dengan bukti fitokimia masih terbatas. Penelitian ini bertujuan untuk mengkaji pemanfaatan tradisional Acorus calamus serta mengidentifikasi metabolit sekundernya sebagai dukungan ilmiah terhadap penggunaan obat tradisionalnya. Penelitian menggunakan pendekatan mixed-method dengan menggabungkan kajian etnobotani kualitatif dan uji fitokimia eksperimental. Data etnobotani dikumpulkan melalui wawancara, observasi, dan dokumentasi dengan melibatkan seorang praktisi pengobatan tradisional di Desa Pengambang Jaya, Provinsi Riau. Analisis fitokimia dilakukan pada ekstrak metanol rimpang menggunakan metode skrining kualitatif standar. Hasil penelitian menunjukkan bahwa rimpang Acorus calamus terutama digunakan sebagai obat tradisional untuk mengatasi demam. Uji fitokimia menunjukkan adanya senyawa fenolik , flavonoid, alkaloid, dan triterpenoid, sedangkan steroid dan saponin tidak terdeteksi. Temuan ini menunjukkan bahwa Acorus calamus mengandung senyawa bioaktif yang berpotensi sebagai obat dan mendukung penggunaan tradisionalnya. Penelitian ini menegaskan pentingnya integrasi pengetahuan tradisional dengan validasi ilmiah dalam penelitian etnobotani.